Differences in Adolescents' Smoking Behavior and Media Exposure to Smoking Advertisements in Urban and Rural Padang City - Hamzah, Prima Kurniati; Faisal, Debri Rizky; Kasra, Kamal; Ilmaskal, Radian; Iqbal, Wira; Yusda Prima Putra, Ikhsan; Surya, Rezi Fatrima; Betasril, Ade (Universitas Airlangga, 2024)
Background: Smoking is a habit that cannot be eliminated and leads to a variety of illnesses and even death. Young people are particularly vulnerable to the effects of electronic and non-electronic media. Aims: The study was to compare cigarette advertising exposure to electronic and non-electronic media among early teenagers in urban and rural Padang. Methods: The research design was cross-sectional. The sample consisted of 266 junior high school students from the city of Padang. Multi-stage random sampling was used to select the sample. Data were collected between 13 March and 4 April 2024. Data were collected through questionnaires and interviews and processed using Stata software version 17. The results revealed differences in smoking behavior and exposure to tobacco advertising media among early adolescents in urban and rural areas. Results: Smoking rates among adolescents in urban and rural areas are 20.54% and 23.38%, respectively. It is clear that in urban areas, 41.67% of adolescents smoke electronic cigarettes, but in rural areas, 72.22% smoke non-electronic cigarettes. There is a clear correlation between smoking habits and exposure to cigarette advertising in rural shops and stalls (p=0.012). Similarly, there is a significant difference in exposure to mobile phones between urban and rural areas (p=0.001 vs. p=0.000). Conclusions: There was a significant association between television viewing habits of films and videos in metropolitan areas (p=0.003) and the frequency of seeing health services.